Magnetic resonance perfusion imaging of resting-state cerebral blood flow in preclinical Huntington's disease - Wolf, Robert Christian; Grön, Georg; Sambataro, Fabio; Vasic, Nenad; Wolf, Nadine D.; Thomann, Philipp; Saft, Carsten; Landwehrmeyer, G Bernhard; Orth, Michael (Journal of cerebral blood flow & metabolism, 2011)
Magnetic resonance imaging (MRI) of the brain could be a powerful tool for discovering early biomarkers in clinically presymptomatic carriers of the Huntington's disease gene mutation (preHD). The aim of this study was to investigate the sensitivity of resting-state perfusion MRI in preHD and to identify neural changes, which could serve as biomarkers for future clinical trials. Differences in regional cerebral blood flow (rCBF) in 18 preHD and 18 controls were assessed with a novel MRI method based on perfusion images obtained with continuous arterial spin labeling. High-resolution structural data were collected to test for changes of brain volume. Compared with controls, preHD individuals showed decreased rCBF in medial and lateral prefrontal regions and increased rCBF in the precuneus. PreHD near to symptom onset additionally showed decreased rCBF in the putamen and increased rCBF in the hippocampus. Network analyses revealed an abnormal lateral prefrontal pattern in preHD far and near to motor onset. These data suggest early changes of frontostriatal baseline perfusion in preHD independent of substantial reductions of gray matter volume. This study also shows the feasibility of detecting neural changes in preHD with a robust MRI technique that would be suitable for longitudinal multisite application.
Gesehen am 24.11.2022